Answer:
Simplifying
5x + x = 54
Combine like terms: 5x + x = 6x
6x = 54
Solving
6x = 54
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Divide each side by '6'.
x = 9
Simplifying
x = 9
Step-by-step explanation:
Answer:
As x increases, the rate of change of f(x) exceeds the rate of change of g(x).
Step-by-step explanation:
Hope this helps :)
Answer:
I think it's A...
Step-by-step explanation:
It's been a little while since I've done polynomials, binomials, monomials, etc., so I think I'm right, but sorry if I'm wrong...
A: 2-3x
First distribute 8-3(x+2) to get
8-3x-6.
Combine like terms to simplify the equation: 8-6=2
And now the answer is 2-3x
The possible dimensions of the prism will be evaluated as follows:
<span>60x3 + 145x2 + 70x
factoring out
factoring out 5x we get:
5x(12x^2+29x+14)
factoring the quadratic we get:
5x(3x+2)(4x+7)
hence the dimensions are:
5x by (3x+2) by (4x+7)</span>